2021
DOI: 10.1037/spq0000468
|View full text |Cite
|
Sign up to set email alerts
|

Teacher stress and anxiety during COVID-19: An empirical study.

Abstract: The purpose of this study was to explore how returning to teaching during the Coronavirus disease (COVID-19) pandemic impacted teachers' stress and anxiety. Specifically, the study investigated how teachers' anxiety changed during the first month of school. Additionally, the study explored the association of teachers' stress and anxiety and predictor variables for changes in teacher anxiety while teaching during the COVID-19 pandemic. The present study included 329 elementary teachers from across the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
130
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 39 publications
16
130
1
1
Order By: Relevance
“…In terms of mental health outcomes, 15.7% of school staff also reported poorer mental health outcomes, which was substantially higher than the general population as reported in the 2012 Canadian Community Health Survey (CCHS) (7.8%) ( Patten et al, 2014 ). While there are no published studies on the mental health of school staff during the second year of the pandemic using this specific question, our results are consistent with growing evidence of poor mental health in teachers during the first year of the pandemic ( Kim et al, 2021 ; Ozamiz-Etxebarria et al, 2021 ; Pressley et al, 2021 ). Further, even though a systematic review concluded that the pandemic may not have caused a long-lasting mental health crisis in the general population ( Robinson et al, 2021 ), our data show the mental health of school staff was worse than that of the general Canadian population during the second year ( Statistics Canada, 2021 ) and during pre-pandemic time periods ( Patten et al, 2014 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In terms of mental health outcomes, 15.7% of school staff also reported poorer mental health outcomes, which was substantially higher than the general population as reported in the 2012 Canadian Community Health Survey (CCHS) (7.8%) ( Patten et al, 2014 ). While there are no published studies on the mental health of school staff during the second year of the pandemic using this specific question, our results are consistent with growing evidence of poor mental health in teachers during the first year of the pandemic ( Kim et al, 2021 ; Ozamiz-Etxebarria et al, 2021 ; Pressley et al, 2021 ). Further, even though a systematic review concluded that the pandemic may not have caused a long-lasting mental health crisis in the general population ( Robinson et al, 2021 ), our data show the mental health of school staff was worse than that of the general Canadian population during the second year ( Statistics Canada, 2021 ) and during pre-pandemic time periods ( Patten et al, 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…School staff are essential workers that play a vital role in educating children and allowing parents to engage more fully in the workforce and support the economy ( Pressley et al, 2021 ). Schools have been at the center of debates around the risk from COVID-19, particularly during the 2020-2021 academic year when, in many parts of the world, schools re-opened.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress caused by the public health measures such as quarantine, isolation, and closures, raises the question of how people will emotionally cope with these new challenges. Certain professions, such as healthcare workers, are at a higher risk of having emotional distress during the pandemic ( 2 ). Another profession that is at higher risk of emotional problems during the pandemic is the teaching profession.…”
Section: Introductionmentioning
confidence: 99%
“…Third, teachers have experienced significant stress during COVID-19 with an increase in anxiety around virtual instruction and communication with parents (Pressley et al, 2021). Moreover, children's loss of learning academic skills (Engzell et al, 2021) combined with the lack of social interactions has created new obstacles for teachers.…”
mentioning
confidence: 99%